Uji Efektivitas Pasta Gigi Pemutih terhadap Perubahan Warna Gigi Ekstrinsik - Bayahu, Cintia; Pengemanan, Damajanty H. C.; Mintjelungan, Christy N. (Universitas Sam Ratulangi, 2021)
Abstract: Physical appearance has a major influence in determining the quality of individual social interaction, especially in terms of non-verbal interactions. Tooth color is one of the things that affect physical appearance. Various efforts to improve the aesthetics of tooth color should be studied further, including the use of whitening toothpaste. This study was aimed to determine the effectiveness of whitening toothpaste on extrinsic tooth discoloration. This was a true experimen-tal study in the form of laboratory test. Coffee was used as a discoloring agent for teeth. Twenty-six premolar teeth were immersed in coffee solution for 14 days. Then the samples were divided into four groups based on the toothpaste used. Initial measurements used the CIEL *a*b* digital dental photo technique. Brushing was carried out for 14 days, after which the tooth color was measured again. The paired sample t-test and the Wilcoxon test showed a significant change in * L values in the group receiving 7% perlite, hydrated silica, and sodium bicarbonate (p=0.01; p=0.001; p=0.012). The Wilcoxon test showed no change in *a and *b values in all whitening toothpaste groups (p>0.05). There was no significant change in the *L *a *b toothpaste (p>0.05). In conclusion, whitening toothpaste is effective against extrinsic tooth discoloration.Keywords: extrinsic tooth discoloration; whitening toothpaste; tooth colorAbstrak: Penampilan fisik memiliki pengaruh besar dalam menentukan kualitas interaksi sosial individu, terutama dalam hal interaksi non-verbal. Salah satu hal yang memengaruhi penampilan fisik individu ialah warna gigi. Berbagai upaya untuk meningkatkan estetika warna gigi harus dikaji lebih lanjut, termasuk penggunaan pasta gigi pemutih. Penelitian ini bertujuan untuk mengetahui efektivitas pasta gigi pemutih terhadap perubahan warna gigi ekstrinsik. Jenis penelitian ialah eksperimental murni (true experimental design) berupa uji laboratorik. Kopi digunakan sebagai bahan diskolorasi untuk gigi. Sebanyak 26 gigi premolar direndam dalam larutan kopi selama 14 hari. Sampel dibagi ke dalam empat kelompok berdasarkan pasta gigi yang digunakan. Pengukuran awal menggunakan teknik digital dental photo CIEL*a*b*. Penyikatan dilakukan selama 14 hari, setelah itu warna gigi diukur kembali. Hasil uji paired sample t-test dan Wilcoxon menunjukkan terdapat perubahan nilai *L yang bermakna pada kelompok yang mendapatkan perlite 7%, silica hydrated, dan sodium bicarbonate (p=0,01; p=0,001; p=0,012). Uji Wilcoxon menunjukkan tidak terdapat perubahan nilai *a dan nilai *b pada semua kelompok pasta gigi pemutih (p>0,05). Pada pasta gigi tanpa pemutih tidak didapatkan perubahan nilai *L*a*b yang bermakna (p>0,05). Simpulan penelitian ini ialah pasta gigi pemutih efektif terhadap perubahan warna gigi ekstrinsik.Kata kunci: perubahan warna gigi ekstrinsik; pasta gigi pemutih; warna gigi